Evaluasi Kualitas Pengungkapan Value at Risk Perbankan Indonesia - Wibowo, Buddi; Fadhila, Hasna (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019)DO - 10.24843/JIAB.2019.v14.i02.p12, 2019)
Market risk measurement of bank investment portfolios is a still problem not only among practitioners, but also among academicians. The accuracy and quality of market risk disclosures are important issues because transparency of the bank risk level encourages market control in the form of market discipline and it also improves the quality of risk management carried out internally by the bank. This research measures the quality of Value at Risk disclosures carried out by Indonesian banks. The accuracy of Value at Risk in this research is measured from the Value at Risk component which contains information of yield volatility of bank trading treasury activities. To measure Value at Risk disclosure, this research runs various methods of Value at Risk measurement. This research shows that Historical Simulation is the most widely used method of measuring Value at Risk by Indonesia banks. The empirical test results however show that using asymmetric volatility gives better quality Value at Risk parametric measures than the historical Value at Risk Simulation method. This research shows that Value at Risk as measured by Historical Simulation method contains the least information on bank trading treasury yields. Keywords : V alue at r isk ; d isclosure ; market r isk ; v olatility